1992
DOI: 10.1002/ajmg.1320430515
|View full text |Cite
|
Sign up to set email alerts
|

Sparse hair and multiple endocrine disorders in two women heterozygous for adrenoleukodystrophy

Abstract: We describe two sisters (40 and 42 years old) heterozygous for adrenoleukodystrophy who have multiple endocrine disorders. In addition to the characteristic neurological symptoms, the younger patient has Addison disease and primary hypothyroidism attributable to autoimmune thyroiditis, and the older one has Graves disease. Both patients have loss of body hair and sparse scalp hair, which have not been reported previously in women heterozygous for adrenoleukodystrophy. After the institution of glucocorticoid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…In fact, in the very ®rst report of a patient with AMN, ®rst areolar, then diffuse alopecia was noted from the age of 8 years: a skin biopsy revealed chronic in¯ammatory in®ltrates in the corium (Budka et al, 1976). Additionally, the coexistence of X-ALD and autoimmune endocrine disease has been reported in several patients (Federico et al, 1988;Dumic et al, 1992). Similarly, in patient Z the biochemical defect of X-ALD and an autoimmune polyglandular syndrome were intertwined.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, in the very ®rst report of a patient with AMN, ®rst areolar, then diffuse alopecia was noted from the age of 8 years: a skin biopsy revealed chronic in¯ammatory in®ltrates in the corium (Budka et al, 1976). Additionally, the coexistence of X-ALD and autoimmune endocrine disease has been reported in several patients (Federico et al, 1988;Dumic et al, 1992). Similarly, in patient Z the biochemical defect of X-ALD and an autoimmune polyglandular syndrome were intertwined.…”
Section: Discussionmentioning
confidence: 95%
“…A disturbed hair growth has frequently been reported in men with ALD/AMN [5, 8, 9, 10, 11, 12, 13, 14, 15]. It was the aim of the present study to further characterize the involvement of hair in AMN.…”
Section: Introductionmentioning
confidence: 83%
“…Remarkably, Dumic et al [10]described 2 sisters who were heterozygous carriers of the ALD gene. They had marked alopecia and sparse body hair and one of them showed, in addition, madarosis and sparse eyebrows.…”
Section: Discussionmentioning
confidence: 99%
“…Females heterozygous for ALD may have loss of body hairs and sparse scalp hair [15]. However, more in-depth investiga tions on hair have not yet been performed in those patients; histology from a bald area of the patient reported by Papini et al [8] showed hypotrophy of the hair follicles and hyper plasia of sebaceous glands.…”
mentioning
confidence: 99%
“…It has been found that these chemicals trigger recep tors (so-called peroxisome-proliferator-associated recep tors, PPAR) that are members of the nuclear hormone receptor superfamily, to which retinoic acid receptors and retinoid X receptors belong [17], A target gene for PPAR has been recently identified, that is the acylcoenzyme A oxidase gene, which encodes the key enzyme of the peroxi somal fatty acid (5-oxidation system [15]. Furthermore, a convergence of PPAR and retinoid-dependent signaling pathways is suggested by the facilitating binding of PPAR to cognate response elements by retinoid X receptor a [18], the ligand of which is 9-cis-retinoic acid.…”
mentioning
confidence: 99%